Necrotic stomatitis and haemorrhagic enteritis in an indian rock python - Balasundara Kavitha Rani; Shekhya Ganga Naik; Konanur Javaregowda Ananda; Basavanal Eswarappa Shambulingappa; Suresh Revanna Patel; Mosarukunte Devaraj (Eurasian Journal of Veterinary Sciences)
Pythons are one of the largest snakes in the world. The Indian rock python bred in zoological garden had suffered from grievous injury on the frontal area of the head was received. A chronic stomatitis was evident with grayish lesions on either side of the lower jaw on the gingival mucosa. The lateral side of the left upper jaw showed partially sloughed skin of the lips hanging from the upper jaw indicating a chronic necrotic reaction. The stomach devoid of ingesta had catarrhal exudate and gastric ulcerations with mild edema. Throughout the small intestine there were petechial haemorrhages and necrotic foci, villous atrophy and the large intestine harboured several nematodes. Grossly, the lungs had catarrhal frothy contents, and microscopically showed alveolar septal thickening, congestion, haemorrhages and edema. Histological investigation of the stomach and intestine indicated epithelial sloughing, congestion, catarrh and bacillary population embedded in the crypts. Liver had focal hepatitis, haemosiderosis and portal fibrosis with biliary proliferation. The post mortem investigation revealed that the cause of death was generalized systemic disease due to chronic necrotic stomatitis, pneumonia and necro-haemorrhagic enteritis.